International Trade and Investment and Food Systems: What We Know, What We Don't Know, and What We Don't Know We Don't Know - Ashley Schram; Belinda Townsend (Kerman University of Medical Sciences, 2021)
BackgroundGlobalised and industrialised food systems contribute to human and planetary health challenges, such as food insecurity, malnutrition, and climate change. International trade and investment can serve as a barrier or enabler to food system transformations that would improve health and environmental outcomes. MethodsThis article used health impact assessment (HIA) to analyse what we know, what we don't know, and what we don't know we don't know about the role that trade and investment might play in food system transformations to improve human and planetary health. ResultsEvidence exists for the link between trade and investment and the spread of unhealthy food commodities, efforts to impede nutrition labelling, and increased concentration of ultra-processed food and beverage product companies. The role of trade and investment in the reduction of animal sources in human diets is emerging and may include challenging measures that restrict the use of terms like 'milk' and 'burger' in plant-based alternatives and the promotion of plantbased foods through non-tariff barriers and targeted efforts at regulatory harmonisation. Trade disputes may serve as the forum for battles around state discrepancies in the safety and acceptability of technological innovation in the food supply, as was the case with hormone treated beef between the European Union (EU) and the United States. Corporate social responsibility (CSR) obligations are unambitious but represent welcome progress in balancing public and private interests. Finally, introducing greater policy flexibility, transparency, and participation provides opportunities to shape a modern trade and investment system that can respond to future food system challenges in a timely fashion. ConclusionResearch at the intersection of trade and investment and food systems should address emergent food systems issues, particularly those that intersect health and climate, while policy efforts should be future-proofing the flexibility of the trade and investment system to enable food system design that supports improved human and planetary health outcomes.